KORELASI KOMITMEN, KOMPETENSI PROFESIONAL, DAN MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA GURU SMK NEGERI DI KOTA ARGA MAKMUR - hendy, Hendy; Nur Sasongko , Rambat; Putri Kartiwi, Asti (Manajer Pendididikan, 2025)
This study examines the correlation of commitment, professional competence, and achievementmotivation to the work productivity of teachers at state vocational schools in the city of Arga Makmur. Theproductivity of school organizations is largely influenced by teacher work productivity. Teacher work productivityshould be an important concern because high and low teacher work productivity can affect the achievement ofoverall school organizational goals. Using a descriptive correlational quantitative approach, data were collectedthrough surveys, documentation, and questionnaires with teachers at State Vocational Schools in Arga MakmurCity, then analyzed using correlation techniques. The results showed a positive and significant correlation betweencommitment, professional competence, and achievement motivation to work productivity. In addition, the fourvariables together contribute significantly to teacher work productivity. This study emphasizes the importance ofmaintaining and improving commitment, professional competence, and achievement motivation to workproductivity. The findings provide insights for principals, teachers, and aspiring educators.